Early development and larval rearing of climbing perch, Anabas testudineus bloch - Ismail, Zalina (2012)
Anabas testudineus or locally known as ‘puyu’ is a freshwater fish species grown in Southeast Asian countries. This study was carried out from March –December 2010 at Aquaculture Experimental Station of Universiti Putra Malaysia. This fish is also known as a species that has a low survival rate during its early life stage and fry. Its Seed production and stock assessment are still poorly understood due the high mortality at first stage of development. In the rearing aspect, high food convertion ratio has been recorded when this fish is reared in hapas and earth ponds using homemade food. The objectives of this study were to induce breed climbing perch (Anabas testudineus) using a commercial hormone preparation (Luteinizing Hormone Releasing Hormone analogue (LHRHa), to observe and record the morphological embryonic development of the A. testudineus and to determine optimal stocking density. The first experiment was conducted to determine its the effectiveness of LHRHa as an agent to induce maturation and ovulation of A. testudineus with the intensity level of 2, 20, 200 μg/kg of body weight and saline as a control. The brooder were injected one time and left to spawn in the aquarium tanks in the sex ratio between male and female as 1:1. The parameters observed include fertilization rate, hatching rate, latency period, eggs production and oocytes diameter. For induced breeding, it was found that all intensity of LHRHa hormone level could enhance the fish to breed with the exception of the control group. It was observed that the fertilized eggs of A. testudineus were almost spherical in shape, clear pearl likes in appearance and free floating on water surface. Egg production was significantly higher in fish treated with 200 μg/kg as compared to fish treated with 2 and 20 μg/kg of body weight of LHRHa hormone while the highest hatching percentage (65.33%) was recorded in fish treated with 2 μg/kg of LHRHa hormone. There was no significant (P>0.05) effect between hormone level on fertilization rate and eggs diameter. The diameters of fertilized eggs ranged from 800 μm-850 μm. For the second experiment, fertilized eggs were obtain through induced spawning and the development of embryos was monitored by sampling embryos at every 30 minutes to 1 h intervals until hatched. The first cleavage occurred at 1:30 h, epiboly began at 5 h, while the embryonic body was formed at 12 h and hatching occurred at 20 h after spawning at water temperature of 26°C. Finally the third experiment was conducted to examine the effect of initial larval density of A. testudineus on growth and survival at three different stocking densities of 35, 55 and 75 larvae/L. Newly hatched larvae of A.testudineus were produced by induced spawning using LHRHa hormone. Results showed that the survival and growth of A. testudineus larvae and fry during 28-day nursing period were stocking density dependent. The highest survival rate 75% was recorded in 35 larvae/L followed by 55 larvae/L (53%) and lastly 75 larvae/L (43%). Water quality parameters like temperature, pH, DO and ammonia ranged from 28.3±0.1°C to 28.3±0.3°C, 8.7±0.1 to 8.8±0.3, 5.7±0.6 to 5.8±0.4 ppm and 0.12±0.22 to 0.18±0.3 ppm respectively, were stable and not influenced by the stocking densities tested. In conclusion, the use of LHRHa was proven to effectively induce maturation and ovulation in A. testudineus and the doses affected the eggs production and hatching rate.